NITROGEN, SULFUR, MICRONUTRIENTS AND INOCULANT IN THE CULTIVATION OF IRRIGATED BEANS IN MATO GROSSO - A. Lange; A. C. Buchelt; O. A. Kobeliski; E. Cavalli; F. J. Wruck; G. Caione (Scientific Electronic Archives, 2017)
This study to evaluate the effects of nitrogen (sources and doses), sulfur, micronutrients and inoculant in the common bean BRS Valente cultivar on winter irrigated crop because in this situation the wrong dose of N at seeding may cause immobilization of the nutrient in the soil and temporary deficiency of N in bean. The experiment took place in 2011, in the city of Sinop – MT, JF farm in the experimental design was randomized blocks with four replications and twelve treatments combining N rates up to 160 kg ha-1, sulfur and inoculation. The following characteristics were evaluated: plant height, height of the first pod, number of seeds per pod, number of pods per plant, 100-seed weight, grain yield in kg ha-1, nitrogen sufficiency index and SPAD index, nitrogen contents in leaf, seeds and plant, nitrogen use efficiency and Pearson correlation. Most variables were influenced by N applications and the highest values were verified in the dose of 160 kg ha-1. The bean yield presented positive and significant correlation with most of the evaluated characteristics and was influenced by nitrogen addition in the system, being the best yield within the highest dose of nitrogen (3262 kg ha-1). Inoculation along with cobalt, molybdenum and 40 kg ha-1 of nitrogen increased yield in comparison with absence of N.